Hubungan Tingkat Stres dengan Kejadian Gastritis pada Masyarakat di UPT Puskesmas Kampa - Novalista, Yolanda; Harahap, Dewi Anggriani; Alini, Alini (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Gastritis is one of the most common and frequently encountered digestive tract problems. Incidence of gastritis can be found in various countries such as England 22%, Japan 14.5%, Canada 35%, France 29.5% and China 31%. In Indonesia, the incidence of gastritis is quite high, namely 40.8%. One of the causes of gastritis is stress which plays a role in increasing stomach acid production. The purpose of this study was to determine the relationship between stress levels and the incidence of gastritis in the community in the working area of the UPT Puskesmas Kampa. This research is a quantitative study using a cross sectional design. This research was conducted at the General and Elderly Polyclinic at the Kampa Health Center, which was conducted on 03-13 October 2022. The population in this study were people seeking treatment at the General and Elderly Polyclinic at the Kampa Health Center, with a total sample of 96 respondents using an accidental sampling technique. The instrument in this study used the Perceived Stress Scale questionnaire (PSS-10). Based on the results of the Chi-Square statistical test analysis, a p value = 0.000 (<0.05) means that there is a significant relationship between stress levels and the incidence of gastritis in the community in the working area of the UPT Puskesmas Kampa. For this reason, the community is expected to be able to avoid the risk factors for gastritis, one of which is stress, so that they can manage stress and not cause gastritis.